Oral cancer-associated tertiary lymphoid structures: gene expression profile and prognostic value. (8th November 2019) - Li, K; Guo, Q; Zhang, X; Dong, X; Liu, W; Zhang, A; Li, Y; Yan, J; Jia, G; Zheng, Z; Tang, W; Pan, L; et al.
Summary: Tertiary lymphoid structure (TLS) provides a local and critical microenvironment for both cellular and humoral immunity and supports effective antigen presentation and lymphocyte activation. However, the gene expression profile and prognostic significance of TLS in oral cancer remain largely unrevealed. In this study, we found the presence of both intratumoral and peritumoral TLSs in a series of 65 patients with oral cancer treated by surgical resection, with positive detection rates of 33.8 and 75.4%, respectively. The presence of intratumoral TLSs, but not peritumoral TLSs, was significantly associated with decreased P53 and Ki67 scores ( P = 0·027 and 0·047, respectively). The survival analyses revealed that oral cancer patients with higher grades of TLSs was associated with improved disease-free survival (DFS) and overall survival (OS) ( P = 0·037 and 0·031, respectively). Gene expression profiling analysis of the cytokines and chemokines responsible for lymph-node neogenesis identified a three-up-regulated-gene set, i.e. IL7, LTB and CXCL13, which was shown to be correlated with human oral cancer-associated TLSs. This study provides a framework for better understanding of oral cancer-associated TLSs and for delineating future innovative prognostic biomarkers and immune therapeutic strategies for oral cancer. Graphical Abstract: